Analysis of Innovative Approaches to the Drying of Raw Cotton in Solar Dryers - Olimovich, Allanazarov Kuldosh; Tursunpulatovich, Saloxitdinov Alisher (European Journal of Life Safety and Stability (2660-9630), 2021)
The article analyzes the current state of solar air dryers and dryers and the results of research and shows the possibilities and advantages of using horizontal type dryers in terms of economic efficiency.